(untitled) (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2026)
In recent years, English media has become an important tool in enhancing language learning due to its accessibility and authentic content. This study examines the impact of English media, including films, TV shows, podcasts, and social media, on learners’ English language skills. A mixed-methods approach was used with 15 undergraduate students aged 18–20 over four weeks. Data were collected through questionnaires, tests, speaking tasks, and interviews. Results show that English media significantly improves vocabulary and listening comprehension due to authentic language input and contextual learning. However, speaking skills showed only moderate improvement, indicating that media exposure alone is not enough for developing productive language abilities. The study concludes that English media is an effective supplementary tool for language learning, but it should be combined with structured speaking practice for balanced skill development.